Narration of the Companions from the Generation after them, From Companions, from the Prophet, Peace and Blessings of Allah be upon Him Collection, Authentication and Study - Abd Alaziz ibn Mukhtar ibn Ibrahim (Journal of Islamic Studies, 2009)
This research is dealing with an important side of Hadith science, that is, the narration of seniors from others who were lower in grade. Part of this is the narration of Companions of the Prophet (Sahabas), my Allah be pleased with them, from the generation after them, from companions. who in turn narrate from the Prophet peace and blessings of Allah be upon him. This type is an important branch. As-Sakhawi Said: This is done by noble characters and pure souls. Al-Hafiz Al-Iraqi, may Allah have mercy upon him mentioned twenty Hadith and quotation of this type. The researcher made efforts to collect these Ahadith from different books, study and judge their authenticity, according to the rules and standards of the Ularnascif Hadith. This study also showed the importance and benefits of this type of Hadith Science. The study concluded with mentioning that the correct Ahadith and quotations in this branch are (6), the fair ones are (5), and the weak & unaccepted are (10) according to what appeared to the researcher.